2005
DOI: 10.1103/physreve.72.020702
|View full text |Cite
|
Sign up to set email alerts
|

Plucking a liquid chord: Mechanical response of a liquid crystal filament

Abstract: This paper describes an investigation of mechanical properties of freely suspended liquid filaments. These unique fluid microstructures may be formed by layered liquid crystalline mesophases. The filaments are electrically deflected and stimulated to mechanical oscillations. Resonance frequencies and damping rates are recorded. We present a model for a basic description of the dynamics, which is used to evaluate and to discuss the forces involved. The dependence of the oscillation parameters upon geometrical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…[3] Examples include the twist-bend nematic phase [3][4][5] characterised by ambidextrous heliconical structure on 10-nm range without layering; the helical nanofilament phase [6] of 30-40 nm wide stack of twisted layers with about 100 nm half pitch and the so-called B7 material [7,8] that forms peculiar micrometre scale helical patterns and slender freely suspended filaments. [9][10][11][12][13][14] The amazing optical B7 textures attracted an intense research that lead to many important findings. [7][8][9]13,[15][16][17][18][19][20][21] Small angle X-ray scattering (SAXS) [7,16,19] studies revealed a number peaks [16,19] that can be indexed by a slightly oblique monoclinic 2D unit cell with a~3-5 nm and b~8-20 nm periodicities.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Examples include the twist-bend nematic phase [3][4][5] characterised by ambidextrous heliconical structure on 10-nm range without layering; the helical nanofilament phase [6] of 30-40 nm wide stack of twisted layers with about 100 nm half pitch and the so-called B7 material [7,8] that forms peculiar micrometre scale helical patterns and slender freely suspended filaments. [9][10][11][12][13][14] The amazing optical B7 textures attracted an intense research that lead to many important findings. [7][8][9]13,[15][16][17][18][19][20][21] Small angle X-ray scattering (SAXS) [7,16,19] studies revealed a number peaks [16,19] that can be indexed by a slightly oblique monoclinic 2D unit cell with a~3-5 nm and b~8-20 nm periodicities.…”
Section: Introductionmentioning
confidence: 99%
“…Lamellar as well as columnar structures are encountered among the bent core ('banana') compounds. It has been shown that several mesophases such as SmCP (where P stands for polar), PM-SmCP (polarization modulated SmC) and B 7 can also form free-standing fibres [3][4][5][6]. Until now, microscopic textures associated with the B 7 phase ('B 7 texture') remained among the most mysterious patterns of the 'banana phases'.…”
Section: Introductionmentioning
confidence: 98%
“…Freely suspended fluid filaments are among the most exotic structures formed by liquid crystalline materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Most of these unique structures are found in some mesophases of bent-core smectogens.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier mechanical and electrical studies explored the dynamical properties of such filaments [6,7,12]. However, still very little is known about their mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation